Maternal and perinatal outcomes in multiple versus singleton pregnancies in Dakar, Senegal: a cross sectional study over 10 years - Ndiaye, Mame D.; Gueye, Mamour; Diop, Ndèye Aissatou; Ndour, Simon B.; Niang, Ndama; Fall, Ndèye G.; Diakhate, Abdoulaye; Diallo, Moussa; Mbaye, Magatte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The birth of twins is a singular event in most societies, and even more when it comes to multiple births. The objective of this study was to investigate maternal and perinatal outcomes in multiple versus singleton pregnancies. Methods: Cross-sectional study carried out at Philippe Maguilen Senghor health center in Dakar, Senegal from January 1, 2011 to June 30, 2019. Data were extracted from this E-perinatal electronic database and then analyzed in statistical package for social science software (SPSS 24, Mac version). Results: A total 42,870 mothers delivered 44,149 newborns including 1250 twins (2.8%) and 29 triplets. The mean maternal age was 27 years. Mothers with multiple pregnancies had 3 times the odds of poor maternal outcome compared to mothers with single pregnancies (OR 2.42, 95% CI; 1.98-2.94, p <0.001, for high blood pressure; OR, 2.66; 95% CI, 2.11-3.32, p= <0.001, for severe pre-eclampsia; and OR, 3.04; 95% CI, 1.64-5.66, p <0.001, for postpartum hemorrhage). Likewise, women with multiple gestations had significantly higher rates of preterm birth (OR 5.62; 95% CI: 4.91-6.41, p <0.001), breech presentations (OR = 11.02; CI = 9.68-12.53, p <0.001) and neonatal deaths (OR = 2.94; CI = 9.6852-12.5328 p= 0.004) as compared to women with singleton gestations. Furthermore, women with multifetal gestations had increased risk for caesarean section (OR 2.14; 95% CI: 1.91-2.41, p <0.001) compared with their singleton counterparts. The risks for episiotomy and perineal injuries were higher for women with singleton gestations as compared to multiple gestation mothers. Conclusions: This study results are in line with previous findings and contradict others. Particular attention should always be paid to multiple pregnancies’ management. However, the pattern of certain complications traditionally correlated with multiple pregnancies is to be confirmed.